Intratumoral microbiome impacts immune infiltrates in tumor microenvironment and predicts prognosis in esophageal squamous cell carcinoma patients - Zhang, Shuyue; Zhang, Shuishen; Ma, Xiaofan; Zhan, Jing; Pan, Chuqing; Zhang, Huizhong; Xie, Xiuying; Wen, Jing; Xie, Xuan (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Different intratumoral microbiomes exist in different tumors and play a crucial function in carcinogenesis. However, whether it impacts clinical outcomes in esophageal squamous cell carcinoma (ESCC) and the mechanism remains unclear. Methods: 16S rDNA amplicon sequencing was performed on surgically resected samples from 98 ESCC patients to analyze intratumoral microbiome abundance and composition. Multiplex fluorescent immunohistochemistry staining was used to profile the phenotypes of immune infiltrates in the tumor microenvironment (TME). Results: Patients with higher intratumoral Shannon index had significantly worse surgical outcomes. When patients were divided into short-term survivors and long-term survivors based on the median survival time, both intratumoral alpha- and beta-diversity were found to be significantly inconsistent, and the relative abundance of Lactobacillus and Leptotrichia emerged as the two microorganisms that probably influenced the survival of ESCC patients. Only Lactobacillus in ESCCs was validated to significantly worsen patients’ prognoses and to be positively correlated with the Shannon index. Multivariate analysis revealed that the intratumoral Shannon index, the relative abundance of Lactobacillus, and the pTNM stage were independently associated with patients’ overall survival. Furthermore, the relative abundance of Lactobacillus and Shannon index were both positively correlated with the proportions of PD-L1+ epithelial cells (ECs) and tumor-associated macrophages (TAMs). Shannon index was negatively correlated with the proportions of natural killer cells (NKs) in the TME. Conclusions: High abundance of intratumoral Lactobacillus and bacterial alpha-diversity was associated with the formation of the immunosuppressive TME, and predicted a poor long-term survival in ESCC patients.